Sellers' inflation, profits and conflict: Why can large firms hike prices in an emergency? - Isabella Weber; Evan Wasner (University of Massachusetts, Department of Economics, 2023)
The dominant view of inflation holds that it is macroeconomic in origin and must always be tackled with macroeconomic tightening. In contrast, we argue that the US COVID-19 inflation is predominantly a sellers' inflation that derives from microeconomic origins, namely the ability of firms with market power to hike prices. Such firms are price makers, but they only engage in price hikes if they expect their competitors to do the same. This requires an implicit agreement which can be coordinated by sector-wide cost shocks and supply bottlenecks. We review the long-standing literature on price-setting in concentrated markets and survey earnings calls and compile firm-level data to derive a three-stage heuristic of the inflationary process: (1) Rising prices in systemically significant upstream sectors due to commodity market dynamics or bottlenecks create windfall profits and provide an impulse for further price hikes. (2) To protect profit margins from rising costs, downstream sectors propagate, or in cases of temporary monopolies due to bottlenecks, amplify price pressures. (3) Labor responds by trying to fend off real wage declines in the conflict stage. We argue that such sellers' inflation generates a general price rise which may be transitory, but can also lead to self-sustaining inflationary spirals under certain conditions. Policy should aim to contain price hikes at the impulse stage to prevent inflation from the onset.
Keywords: D21; D22; D43; E31; E53; 330; pricing behavior; market power; conflict inflation; profits; monetary policy